Chlorpromazine versus thiothixene for people with schizophrenia (Protocol) - Cardosa, Daniel; Wakeham, Joseph; Shaw, Philippa Amy; Dutton, Brittany; Wildman, Levine (Wiley, 2017)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To review the effects of chlorpromazine compared with thiothixene for people with schizophrenia.